Recycling of used lubrication oil by solvent extraction-A guideline for single solvent design - O. M., Nimir; M. I., Abdul Mutalib; R., Adnan (1997)
Solvent extraction has been known as one of the potential techniques for recycling used lubricating oil. The technique has received considerable attention due to the advantages that it offers practically from environmental and economic points of view. Different organic solvents have been used to flocculate the deteriorated additives and impurities which presence in the form of fine suspension in the used lubricating oil prior to recovering the oil. This works attempts to study the performance of three types of solvents i.e. 2-Propanol, Butanol and MEK, in the extraction process for recovering used lubricating oil. Temperature and the weight ratio of solvent to oil were used as the key operating parameters in the study. The relation between these parameters and the performance of the individual solvents (describes in the form of percent sludge removal and percent oil losses) was investigated to see if some form of general and useful guidelines can be developed especially for predicting best operating region for a specific single solvent. The guideline developed is useful at the early stage of design where it is important to select proper solvent and to determine the best operating condition for such solvent.